2009
DOI: 10.1080/00036840601007237
|View full text |Cite
|
Sign up to set email alerts
|

Markets segmented by regional-origin labelling with quality control

Abstract: It is the objective of this paper to provide a methodological framework for the analysis of regional marketing programs which inlclude regional-origin labelling as well as quality assurance and control. Such programs are increasingly being introduced in Europe and other parts of the world as a means against quality uncertainty in globalized markets. An equilibrim - displacement model is developed for a segmented market with differential qualities that can be utilized for a broad variety of marketing programs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…The study objective was to assess some of the economic aspects of the PGI label, such as the economic performance, profitability and technical efficiency of a sample of farms. Although the relatively limited scope of the study restricts the generalization of the results, it is possible to draw valid conclusions while still acknowledging, along with other authors (Bosmans et al, 2005;OECD, 2006;Anders et al, 2009), the need for further research on a wider scale, incorporating new analytical techniques.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The study objective was to assess some of the economic aspects of the PGI label, such as the economic performance, profitability and technical efficiency of a sample of farms. Although the relatively limited scope of the study restricts the generalization of the results, it is possible to draw valid conclusions while still acknowledging, along with other authors (Bosmans et al, 2005;OECD, 2006;Anders et al, 2009), the need for further research on a wider scale, incorporating new analytical techniques.…”
Section: Discussionmentioning
confidence: 70%
“…Recently, in view of the scarcity of existing studies on this subject (Bosmans et al, 2005;Anders et al, 2009) the OECD (2006) drew attention to the need for research to analyse livestock farm performance variation related to the adoption of different marketing strategies. The second objective of the study reported here, therefore, was to compare the performance of PGI-certified and noncertified farms.…”
mentioning
confidence: 99%
“…Anders et al. () used an equilibrium displacement model for markets segmented by regional‐origin labelling and quality to investigate the role of governmental support on farmers' welfare. They found that welfare implications for producers crucially depend on the costs of participation, including quality control, and on the co‐financing mechanism between the government and producers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors suggested that countries must select their GIs very carefully as the confluence of product familiarity in international markets and land ownerships patterns that are needed for the generation and widespread distribution of benefits will be rare events. Anders et al (2009) used an equilibrium displacement model for markets segmented by regional-origin labelling and quality to investigate the role of governmental support on farmers' welfare. They found that welfare implications for producers crucially depend on the costs of participation, including quality control, and on the co-financing mechanism between the government and producers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, the classifications provide a means to implement quality and consumer information policies, as well as serve as rural development tools. Traditional production methods, especially in livestock holding, tend to be found in less-favored areas (Barham, 2003;Gilg & Battershill, 1998;Marsden, Banks, & Bristow, 2000;Re´viron, Chappuis, & Barjolle, 2004) and the production distinction is intended to raise farmers' income in such areas (Anders, Thompson, & Herrmann, 2007). However, although products with a geographical origin can contribute towards rural development, successful implementation depends not on the institutionalization of origin as a resource, but on the approach used to undertake the process and the design of efficient value-added strategies (Sylvander, 2004).…”
Section: Introductionmentioning
confidence: 98%